Komunikasi Visual Pengenalan Tanjak Dan Rumpak Sebagai Pelengkap Pakaian Adat Khas Palembang - Novriansyah Wirawan; Husni Mubarat; Aji Windu Viatra (Penerbit dan Percetakan, CV. Picmotiv, 2024)
Songket is a fabric originating from Palembang, the process of making songket fabric uses gold and silk threads, which gives the fabric a shine and luxury. Songket cloth is also used in other traditional clothing such as Tanjak and Rumpak. Tanjak is a headband commonly worn by men in Palembang city. In addition to Tanjak Rumpak is also a traditional clothing of Palembang city which is worn on the waist of men as a complement to the typical Palembang traditional clothing. Along with the changing times there are many mistakes in the use of Tanjak and Rumpak such as wearing Rumpak below the knee used by single or unmarried men. Therefore, this design aims to create a promotional media for this typical Palembang traditional clothing to be better known for its history by the wider community in Palembang city. This promotional media design uses the 5W+1H method which focuses on innovation by utilizing designer tools. This approach aims to combine technology, user needs, and cleanliness. The result of this design is that an effective and attractive visual approach is very important. This helps to increase the awareness and appreciation of people in Palembang City towards Tanjak and Rumpak,.